2016
DOI: 10.1007/s13280-016-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and abandonment determine different tree dynamics in wood-pastures

Abstract: Wood-pastures are threatened biotopes in which trees and livestock grazing maintain high conservation values. However, browsing may threaten tree regeneration, whereas abandonment leads to tree encroachment. We studied the regeneration of trees in a grazed and abandoned boreal wood-pastures. In grazed sites, the density of young spruces (Picea abies) was high, while the density of young birches (Betula spp.) was very low. Sprucification can be prevented only by removing spruces. The number of young birches and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Abandoned wood-pastures develop secondary woodlands (normally Norway spruce in Sweden) which reduces biodiversity (Paltto et al 2011 ). In boreal Finland, Oldén et al ( 2017 ) showed that spruce regeneration was abundant in all kinds of abandoned wood-pastures (birch-, pine-, spruce- and broadleaved-mixed dominated wood-pastures) and regeneration was only reduced by removal or by increasing canopy openness. In our experimental study spruce was avoided.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abandoned wood-pastures develop secondary woodlands (normally Norway spruce in Sweden) which reduces biodiversity (Paltto et al 2011 ). In boreal Finland, Oldén et al ( 2017 ) showed that spruce regeneration was abundant in all kinds of abandoned wood-pastures (birch-, pine-, spruce- and broadleaved-mixed dominated wood-pastures) and regeneration was only reduced by removal or by increasing canopy openness. In our experimental study spruce was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental study spruce was avoided. In this regard, Oldén et al ( 2017 ) concluded that sprucification is a major problem in wood-pastures due to resulting landscape homogenization and vegetation compositional changes towards spruce-dominated wood-pastures and suggested spruce regeneration removal to benefit rare plant and insect species characteristic of semi-open woodlands (Oldén et al 2017 ). A recent study reported that 66% of the most valuable oak wood-pasture habitats in Östergötland (Sweden) were abandoned (with subsequent secondary woodland development) and grazing could not be resumed due to lack of farmers and livestock (Garrido et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…>100 years) on natural ecosystem recovery. In boreal forests, there is unexpected recent evidence that natural recovery following cessation of active land-use can in the long term lead to less diverse ecosystems (Oldén et al 2017), but the authors suggest that on the landscape scale biodiversity nonetheless increases with passive recovery (Oldén et al 2017). Other studies show that recovery in disturbance-driven habitats may lead toward the targeted undisturbed ecosystem (Nikodemus et al 2012;Johnson et al 2014;Tikkanen et al 2014).…”
Section: Introductionmentioning
confidence: 99%